Assessing the Impact of Point-of-Sale Beer Brand Ads Through Consumer Neuroscience Research - Lukić, Darko; Starčević, Slađana; Pitić, Goran (Naše gospodarstvo/Our economy, 2025)
This study employs EEG and eye-tracking to assess how brand equity, creative complexity, and spatial layout influence implicit consumer responses to point-of-sale (POS) beer advertisements. Through the theoretical lens of predictive coding and processing fluency, laboratory testing with Serbian beer consumers (N = 20) revealed that simpler designs yielded superior attention performance across TFD and TTFF (d up to 2.62), independent of brand strength. Spatial repositioning reduced packshot detection time by 0.89s (p
Keywords: Consumer Neuroscience; Brand Equity; EEG; Eye-Tracking; Visual Attention